Past Negative Time Perspective as a Predictor of Grade Point Average in Occupational Therapy Doctoral Students - Pat J. Precin (Scholarworks @ WMU, 2017)
Time perspective is a fundamental dimension in psychological time, dividing human experiences into past, present, and future. Time perspective influences individuals' functioning in all occupations, including education. Previous research has examined the relationship between time perspective and academic outcomes, but the same research has not been done, to date, with occupational therapy doctoral students. This quantitative, cross-sectional study investigated the relationship between time perspective and academic success in occupational therapy doctoral students across the United States. Data from the Zimbardo Time Perspective Inventory (ZTPI) and grade point averages (GPAs) were collected from 50 participants via surveymonkey.com. Past Negative time perspective statistically predicted GPA in the negative direction (p = .001) for students in pre-professional OTD programs, but did not predict GPA for post-professional students. Age, gender, and learning environment did not significantly influence the prediction of GPA in either group. The method and results of this study demonstrate that the ZTPI, an instrument used in the field of psychology, may have value in the profession of occupational therapy and occupational therapy doctoral programs.